- TINGKAT PENGETAHUAN MENGENAI ANATOMI FISIOLOGI ANKLE, ANKLE SPRAIN DAN PENANGANANNYA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA ANGKATAN 2020 - Sitepu, Amanda Viani Maria; Karmaya, I Nyoman Mangku; Wardana, I Nyoman Gede; Widianti, I Gusti Ayu (E-Jurnal Medika Udayana, 2023)
Ankle sprain is a tear in the ankle ligaments which is usually caused by an inversion error that can cause movement disorders in the ankle. This study was conducted to determine the level of knowledge of students of the Faculty of Medicine, Udayana University batch 2020 regarding the anatomy and physiology of the ankle, as well as ankle sprains and their treatment. This research was conducted with a descriptive cross-sectional method. The sampling technique used was stratified random sampling method. The research subjects were 87 students from the 2020 Faculty of Medicine. Data collection process was conducted online to assess the level of knowledge about ankle sprains. Data were analyzed using SPSS version 20. The results showed that 28 students (32.2%) had a good level of knowledge, 54 students had a sufficient level of knowledge (62.1%), and 5 students had a low level of knowledge (5.7%). The knowledge level of the majority students of the Faculty of Medicine, Udayana University year 2020 regarding the anatomy physiology of the ankle, ankle sprain, and its management are in the sufficient category. Education through lectures, seminars, or workshop that aims to increase awareness of the importance of knowing ankle sprain and its management needs to be implemented. Keywords: ankle, ankle sprain, knowledge, medical students